Pengaruh Model Pembelajaran Proyek Warga Global Terhadap Civic Virtue Peserta Didik - Sutrisno Sutrisno; Ambiro Puji Asmaroini; Sunarto; Della Futvy Sekarningrum (Integralistik, 2026)
This study aims to systematically measure and analyze the effect of implementing the global citizen project model on the development of Civic Virtue attitudes in students. using a quantitative approach of associative pre-experimental designs with the One-Group Pretest-Posttest Design research method carried out on one experimental group without a control group. data collection with pre-test and post-test, questionnaires, and documentation. Using parried sample T test analysis, simple linear regression and coefficient of determination, with a sample of 32 respondents in the experimental class. The results of the study showed that the global citizen project learning model had a positive and significant effect on the Civic Virtue of students at SMAN 1 Babadan. The ability of the global citizen project (X) in explaining the Civic Virtue value (Y) was 76.7% and the remaining 23.3% was explained by the influence of other variables not studied by the researcher. The implications of the results of this study indicate that learning using a systematic model will affect the characteristics of students, so this needs to be considered by teachers when implementing learning in the classroom so that learning objectives are achieved by paying attention to the influence on student characteristics.